POST-COVID PNEUMONIA AND PULMONARY COMPLICATIONS: A STUDY OF LONG-TERM SEQUELAE AND TREATMENT METHODS IN PATIENTS RECOVERING FROM COVID-19 (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This analysis explores the pathophysiology, clinical features, diagnostic methods, and treatment strategies for post-COVID-19 pneumonia and related pulmonary complications. Based on recent clinical data and longitudinal studies, approximately 30–40% of hospitalized COVID-19 patients experience lasting lung abnormalities beyond the acute phase. The study highlights the multifactorial nature of post-viral complications such as organizing pneumonia, pulmonary fibrosis, and chronic inflammation. Evidence shows that early anti-inflammatory treatment, pulmonary rehabilitation, and structured follow-up improve long-term outcomes. The findings emphasize the need for dedicated post-COVID care clinics and standardized treatment protocols to manage these complex conditions, offering valuable guidance for clinicians treating COVID-19 survivors with ongoing respiratory issues.